Ternary VOCl single-crystal as efficient gate dielectric for 2D field-effect transistors. (24th December 2020) - Zhu, W; Cui, Q; Adam, M L; Liu, Z; Zhang, L; Dai, Z; Yin, Y; Chen, S; Song, L
Abstract: Field-effect transistors (FETs) based on van der Waals heterostructures without the traditional lattice mismatch constraints are highly promising for electronics. As the devices' scale decreases, it is crucial to find a dielectric layer with a high dielectric constant to ensure gate capacitance and low leakage current. Herein, a layered insulator VOCl single crystal synthesized by chemical vapor transport is demonstrated as a high-performance gate dielectric. Notably, the dielectric constant of VOCl can reach up to 11.7, estimated through measuring the capacitance of the metal–insulator-metal device. The MoSe2 FET with VOCl dielectric exhibits a significant decrease in the subthreshold swing from 4906 to 169 mV dec −1, indicating a low trap density at the interface of MoSe2 /VOCl. Besides, the threshold voltage ( V th ) of bottom-gated MoSe2 FET is as low as 0.2 V, further confirming the high potential of VOCl as an ideal two-dimensional gate dielectric.